Collaborative webinar on scopus bibliometric reporting for SIMAD University / Sazlina Saleh - Saleh, Sazlina (Perpustakaan Tengku Anis, 2023)
MACHANG, 21 November - Perpustakaan Tengku Anis (PTA) have successfully organized Collaborative Webinar on Scopus Bibliometric Reporting for SIMAD University. This webinar was held on 21st November 2023 and was done live through PTA's YouTube Channel. This webinar began with the keynote speech from Ts. Hj. Azizi Hj. Jantan, Acting Chief Librarian, Perpustakaan Tun Abdul Razak and continued with keynote speech from Mr. Mohamud Mohamed Siad, Chief Librarian from SIMAD University Library. The objectives of this webinar are to introduce basic fundamentals of bibliometrics, knowledge sharing for example of bibliometric paper in journals and also proposed bibliometric reporting for SIMAD University Library.